Decoding connections in the European population: serum uric acid, sex hormone-binding globulin, total testosterone, estradiol, and female infertility – advanced bidirectional and mediative Mendelian randomization - Tan, Zilong; Shen, Jianwu; Huang, Yuxiao; Li, Junru; Ding, Mengdi; Sun, Aochuan; Hong, Jing; Yang, Yan; He, Sheng; Zhu, Xueying; Luo, Ran (Frontiers in Endocrinology, 2024)
Background Despite observational links between serum uric acid (SUA), sex hormone-related phenotypes, and female infertility, the causality behind these associations remains uncertain. Objective This study utilizes Bidirectional Two-Sample and Mediation Mendelian Randomization to explore the causal relationships and mediation effects of sex hormone-binding globulin (SHBG), total testosterone (TT), and estradiol on these associations. Methods We analyzed single-nucleotide polymorphisms (SNPs) associated with SUA and sex hormone levels using data from large-scale GWAS of European populations. Female infertility data were sourced from 6,481 cases and 75,450 controls in the FinnGen Consortium. We employed methods including Inverse Variance Weighted (IVW), Weighted Median, and MR-Egger regression to assess causality. Results We found that elevated SUA levels causally increase the risk of female infertility (IVW OR: 1.13, P=0.047). Elevated SUA levels significantly decrease SHBG levels (β=-0.261; P=2.177e-04), with SHBG mediating 27.93% of the effect of SUA on infertility (OR=0.854; 95%CI, 0.793–0.920; P=2.853e-05). Additionally, elevated TT levels, which were associated with decreased SUA levels (β=-0.127), showed an indirect effect on infertility mediated by SUA (β=-0.0187; 95% CI, -0.041 to -0.003; P=0.046). Conclusion Our findings demonstrate causal links between high SUA and increased risk of female infertility mediated by hormonal factors such as SHBG and TT. These insights suggest new avenues for infertility treatment and highlight the need for further research into these mechanisms.